2021
DOI: 10.15407/ubj93.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress suppression contributes to antiseizure action of axitinib and rapamycin in pentylenetetrazol-induced kindling

Abstract: Rapamycin and axitinib block different kinases in signaling pathways such as PI3K-Akt-mTOR and BDNF-TrkB, respectively. Both have antiseizure and antioxidative actions, which justify studying the combined effects of these drugs upon seizures and oxidative stress in the chronic model of epilepsy. The investigation aimed to look for the combined effect of rapamycin and axitinib upon pentylenetetrazol (PTZ)-kindled seizures and oxidative stress. Experiments were performed on 300 two-to four-month-old Wistar male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Earlier, we demonstrated that combined administration of rapamycin-blocker of mTOR and axitinib-blocker of tyrosine kinase B caused synergy antiseizure action [6]. Such a synergy developed in parallel with the pronounced antioxidant effects precipitation [6].…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Earlier, we demonstrated that combined administration of rapamycin-blocker of mTOR and axitinib-blocker of tyrosine kinase B caused synergy antiseizure action [6]. Such a synergy developed in parallel with the pronounced antioxidant effects precipitation [6].…”
Section: Introductionmentioning
confidence: 81%
“…Based on the results of previous studies [6], the drugs with different mechanisms of action -mTOR inhibitor rapamycin and tyrosine-kinase B inhibitor axitinib were selected for the investigation of their antiseizure action upon immunohistochemical markers of PTZ-induced kindling seizures. Namely, such markers of chronic epilepsy as HIF-1α, TNF-α, and NF-kB levels in the dorsal hippocampus of fully kindled animals were measured following the earlier described method [17,18].…”
Section: Planning (Methodology) Of the Researchmentioning
confidence: 99%
See 3 more Smart Citations